Makna Loyalitas Konsumen Brand Lokal di Era Digital : Studi Fenomenologi terhadap Pengguna Media Sosial - Ibrahim , Ibrahim; Suriyanti Mangkoma; Imaduddin Imaduddin (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2025)
The rise of social media has fundamentally transformed how consumers build loyalty toward brands, particularly local brands. Loyalty is no longer limited to repeat purchases but has expanded into emotional, social, and participatory engagement manifested on digital platforms such as Instagram and TikTok. This study aims to explore and understand the meaning of consumer loyalty toward local brands on social media using a qualitative phenomenological approach. Informants were selected purposively, consisting of eight active users aged 18–35 residing in South Sulawesi who have consistently interacted with local brands through social media. Data collection techniques included in-depth interviews, participatory observation, and digital documentation. Thematic analysis was employed to identify the essential meanings embedded in participants’ experiences. The findings revealed three main themes: loyalty as digital togetherness, value identification with local brands, and social interaction as a form of emotional attachment. The study concludes that consumer loyalty in the digital era is a construction of experience that is reflective, affective, and social in nature. This research contributes to the development of an experience-based perspective on loyalty and offers practical implications for digital strategies of local brands in Indonesia.